Evaluating the Security of Electronic Banking in Users Opinion and Analyzing the Behavior of Banks in the Event of a Security Incident - Popik, Anna; Gryglicka, Agnieszka (Journal of Finance and Financial Law, 2022)
The purpose of this article. The aim of the article is to identify the opinions of bank customers on the level of security of electronic banking in Poland and to analyze the actions taken by banks in the event of a security incident. Methodology. The analysis was based on data collected through a questionnaire survey. The survey with non-random sampling involved 222 people, and 217 records were included in the analysis. The form contained closed questions. The result of the research. The analysis of the survey results indicates a high sense of security among bank account users, especially thanks to campaigns initiated by banks that inform customers about possible dangers. Respondents value direct communication and quick responses, which in this age of technological advances are the most important element in protecting customers. The literature review, which complements the survey, also confirms the high commitment of banking institutions in ensuring security. Despite the analysis of the survey results, it is important to bear in mind the lack of their translation to the general population, which does not allow a clear confirmation of the total security of customers holding funds in bank accounts.